Functional Ionic Liquids Promoted Double Michael Reaction of Benzofuran‐3‐one or 1‐Indone and Symmetric Dienones: Construction of Spiro[benzofuran‐2, 1'‐cyclohexane]‐3‐one or Spiro[cyclohexane‐1, 2'‐indene]‐1', 4(3'H)‐dione Derivatives. Issue 8 (29th May 2017) - Liu, Chunhui; Xu, Yalun; Niu, Songyang; Wei, Liquan; Liu, Yong; Wang, Yanbo; Zhu, Junyan; Fu, Jiya; Yuan, Jinfang
Abstract : The double Michael reactions between benzofuran‐3‐one or 1‐indone and symmetric dienones in the presence of catalytic ionic liquids were successfully developed and spiro[benzofuran‐2, 1'‐cyclohexane]‐3‐one or spiro[cyclohexane‐1, 2'‐indene]‐1', 4(3' H )‐dione derivatives containing a spiro quaternary stereogenic center, which widely exist in biologically active products and building blocks in organic synthesis, were obtained in excellent yields (up to 99%). This catalytic system was also extended to the double Michael reaction of less reactive 1‐indone and the desired products were also obtained in 31%‐62% yields. The catalytic system was highly active and efficient for a broad of substrates under mild conditions. Abstract : The double Michael reactions between benzofuran‐3‐one or 1‐indone and symmetric dienones in the presence of catalytic ionic liquids were successfully developed and the desired products were obtained in excellent yields (up to 99%). This catalytic system was also extended to the double Michael reaction of less reactive 1‐indone and the desired products were obtained in 31%‐62% yields.